(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Effective company performance can cause a company to compete, survive and can increase investor confidence. Therefore the company’s performance needs to be improved better. Company performance in SOEs is measured using a balance scorecard. The purpose of this study is to analyze the effectiveness of company performance on SOEs in the city of Bandung. Research methods using explanatory research. The sampling technique with nonprobability sampling is saturated sampling of 39 people. The data quality test using the validity test and reliability test. Based on the results of the study showed that the company’s performance on SOEs in the city of Bandung has been effective.